'You're a brick': colloquialism and the history of moral concepts. Issue 3 (3rd April 2019) - Krishna, Nakul
ABSTRACT: The Victorian period in Britain saw the curious emergence of the word 'brick' as a term of high praise, picking out for commendation certain qualities of character: reliability and a lack of whimsy. The novels and everyday conversation of the period were full of such phrases as 'you're a brick' or 'he's a regular brick'. In this paper, I trace the history of this phrase in the respectable as well as popular literature of the period, including some ironic attempts to claim for it a classical pedigree. I offer some hypotheses about how we might understand the metaphor of the brick in terms of the needs and values of mainstream British (and more generally, imperial) culture in the period. As an illuminating contrast, I consider the fate of a similar metaphor from mid-twentieth-century culture, 'square', which picks out roughly similar qualities of character but to reprove them. I conclude with some theoretical reflections on how the study of outdated colloquialisms might bring the resources of historical linguistics to bear on the study of the history of moral concepts.